1985
DOI: 10.1159/000249541
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Pustular Psoriasis in a Child

Abstract: We present the first report of the management of generalized pustular psoriasis (Zumbusch pattern) in a young child with etretinate (Tigason). Striking features were the low dosage required to control the disease (as little as 10 mg per week) and the eventual transition of the clinical features to those of psoriasis vulgaris.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 5 publications
0
29
0
1
Order By: Relevance
“…In all, 21 studies were identified, 46,49,50,52,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] but 5 studies were excluded because of an unclear outcome measure, 46,67-70 9 because they used systemic antipsoriatic combination therapies, 49,50,52,[71][72][73][74][75][76] and one case report because there was no clear diagnosis of psoriasis. 77 Therefore, 6 studies remained: 4 studies were classified as LOE 4 61,63-65 ; two were classified as LOE 5.…”
Section: Retinoidsmentioning
confidence: 99%
See 3 more Smart Citations
“…In all, 21 studies were identified, 46,49,50,52,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] but 5 studies were excluded because of an unclear outcome measure, 46,67-70 9 because they used systemic antipsoriatic combination therapies, 49,50,52,[71][72][73][74][75][76] and one case report because there was no clear diagnosis of psoriasis. 77 Therefore, 6 studies remained: 4 studies were classified as LOE 4 61,63-65 ; two were classified as LOE 5.…”
Section: Retinoidsmentioning
confidence: 99%
“…77 Therefore, 6 studies remained: 4 studies were classified as LOE 4 61,63-65 ; two were classified as LOE 5. 62,66 In 1988 a retrospective review of 10 cases was performed 61 in which etretinate was used at an initial dose of 1 mg/kg/d, with a treatment duration varying from 3 weeks to more than 12 months. All patients with pustular psoriasis (n = 5) achieved complete clearance of lesions; in contrast, the erythrodermic psoriasis subgroup (n = 5) showed a complete clearance of lesions in only two, and an improvement in the remaining 3 cases.…”
Section: Retinoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psoriasis genetik yatkınlığı olan bireylerde, uygun tetikleyici faktörlerin araya girmesi sonucu immün sistemin aktivasyonu, inflamasyonu sınırlayan mekanizmaların bozukluğu ve keratinositlerin hiperreaktivitesi ile ortaya çıkmaktadır 1 . Adipoz doku; olgun adiposit, preadiposit, vasküler, nöral ve immun hücrelerden oluşan metabolik olarak aktif bir dokudur.…”
Section: Gi Riflunclassified